The emerging importance of lymphangiogenesis in aging and aging-associated diseases - Ji, Rui-Cheng (Mechanisms of ageing and development, 2024)
Lymphatic aging represented by cellular and functional changes, is involved in increased geriatric disorders, but the intersection between aging and lymphatic modulation is less clear. Lymphatic vessels play an essential role in maintaining tissue fluid homeostasis, regulating immune function, and promoting macromolecular transport. Lymphangiogenesis and lymphatic remodeling following cellular senescence and organ deterioration are crosslinked with the progression of some lymphatic-associated diseases, e.g., atherosclerosis, inflammation, lymphoedema, and cancer. Age-related detrimental tissue changes may occur in lymphatic vessels with diverse etiologies, and gradually shift towards chronic low-grade inflammation, so-called inflammaging, and lead to decreased immune response. The investigation of the relationship between advanced age and organ deterioration is becoming an area of rapidly increasing significance in lymphatic biology and medicine. Here we highlight the emerging importance of lymphangiogenesis and lymphatic remodeling in the regulation of aging-related pathological processes, which will help to find new avenues for effective intervention to promote healthy aging. •Lymphatic aging represented by cellular and functional changes is an increased risk factor for geriatric disorders.•Advanced age and organ deterioration are crosslinked with the progression of some lymphatic-associated diseases.•Lymphangiogenesis and lymphatic remodeling are involved in the regulation of aging-related pathological processes.•Targeting aging-induced lymphatic dysfunction will help to reduce the burden of age-related diseases.